Peningkatan Higher Order Thinking Skills melalui Penerapan Open Ended Play pada Anak Usia 5-6 Tahun - I Wayan Sutama; Nur Anisa; Wuri Astuti; Farah Bella Sukma Rahmawati; Gracia Cahya Wahyudi (Faculty of Education Universitas Negeri Malang, 2022)
Abstract: The learning process has not directed children to develop higher-level thinking skills. Open ended play strategies provide opportunities for children to improve their imagination and cognitive skills. The purpose of this study was to analyze the improvement of the quality of learning and higher order thinking skills in children aged 5-6 years through the application of open ended play. This research uses classroom action research using the Kemmis & Taggart model and is carried out in two cycles. The subjects in this study were 13 kindergarten students with an age range of 5-6 years. Collecting data are using interviews and observations using instruments in the form of observation sheets, field notes, and interview guidelines. Data analysis techniques consist of quantitative and qualitative. Qualitative data includes the stages of data reduction, data presentation and drawing conclusions. Quantitative data were analyzed by the percentage formula. The results showed that the application of open ended play made learning more effective, dancing and efficient in developing higer order thinking skills in children aged 5-6 years. The application of open ended play can improve the higer order thinking skills of children aged 5-6 years. Abstrak: Proses pembelajaran belum mengarahkan anak untuk mengembangkan keterampilan kerpikir tingkat yang lebih tinggi. Open ended play strategy memberikan kesempatan kepada anak untuk meningkatkan daya imajinasi dan keterampilan kognitif. Tujuan penelitian ini adalah untuk menganalisis peningkatan kualitas pembelajaran dan kemampuan berpikir tingkat tinggi pada anak usia 5-6 tahun melalui penerapan open ended play. Penelitian ini menggunakan jenis penelitian tindakan kelas menggunakan model Kemmis & Taggart dan dilaksanakan sebanyak dua siklus. Subjek pada penelitian ini adalah 13 siswa TK dengan rentang usia antara 5-6 tahun. Pengumpulan data menggunakan wawancara dan observasi dengan menggunakan instrument berupa lembar observasi, catatan lapangan, dan pedoman wawancara. Teknik analisis data terdiri dari kuantitatif dan kualitatif. Data kualitatif meliputi tahapan reduksi data, penyajian data dan penarikan kesimpulan. Data kuantitatif dianalisis dengan rumus persentase. Hasil penelitian menunjukkan bahwa penerapan open ended play membuat pembelajaran menjadi lebih efektif, menari dan efisien dalam mengembangkan higer order thinking skills pada anak usia 5-6 tahun. Penerapan open ended play dapat meningkatkan higer order thinking skills anak usia 5-6 tahun.